2020
DOI: 10.1098/rstb.2019.0488
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of haem-binding protein from Arabidopsis thaliana and Cyanidioschyzon merolae

Abstract: Chloroplast biogenesis involves the coordinated expression of the plastid and nuclear genomes, requiring information to be sent from the nucleus to the developing chloroplasts and vice versa. Although it is well known how the nucleus controls chloroplast development, it is still poorly understood how the plastid communicates with the nucleus. Currently, haem is proposed as a plastid-to-nucleus (retrograde) signal that is involved in various physiological regulations, such as photosynthesis-associated nuclear g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Finally, two recent studies identified other haem‐binding candidate proteins from Arabidopsis. These include tau class glutathione S ‐transferases (Sylvestre‐Gonon et al ., 2020) and proteins belonging to the exportin, RNA helicase and basic helix‐loop‐helix families, for instance (Shimizu et al ., 2020). Interestingly, several of these candidates are cytosolic or nuclear proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, two recent studies identified other haem‐binding candidate proteins from Arabidopsis. These include tau class glutathione S ‐transferases (Sylvestre‐Gonon et al ., 2020) and proteins belonging to the exportin, RNA helicase and basic helix‐loop‐helix families, for instance (Shimizu et al ., 2020). Interestingly, several of these candidates are cytosolic or nuclear proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond its diverse functions to serve as cofactors of hemoproteins in various organelles (Layer et al, 2010), several recent studies pose heme as a retrograde signal that is involved in various physiological regulations (Mense and Zhang, 2006;Von Gromoff et al, 2008). Besides, biochemical evidence corroborates this, i.e., half of the identified heme-binding proteins localize in the nucleus in plants (Shimizu et al, 2020). Measuring or monitoring heme content during de novo organogenesis and in the CZ of the SAM of intact plants will provide us with a new insight into the role of the heme branch in nuclear gene expression.…”
Section: Conclusion and Perspectivementioning
confidence: 85%
“…At present, it is unknown whether FC1-derived heme affects the chloroplast processes, such as transcription, editing, translation, and import ( Figure 2 ). Previous proteomic analysis of heme-binding protein detected none of the GUN1-interacting proteins in Arabidopsis [ 72 ]. Therefore, further study is required to elucidate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of heme-binding proteins has identified several novel extraplastidic proteins, including nuclear-localized transcription factors, histone deacetylases, and RNA helicases from Arabidopsis and Cy. merolae [ 72 ]. Further clarification of these putative heme-binding proteins may be necessary for elucidating the heme signaling pathway.…”
Section: Identification Of Gun Mutantsmentioning
confidence: 99%